Investigation of Red Deer (Cervus elaphus) antlers in the Ukrainian Steppe and results - Volokh, Anatolii; Волох, Анатолій Михайлович; Волох, Анатолий Михайлович (My University, 2015)
From 1918–2010, 415 red deer were resettled on the steppe zone territory of Ukraine, 53.0 % of which were complex hybrids bred in the “Askania-Nova” Reserve. Several populations of deer were created as a result, the largest of which is located on the Biriuchy Peninsula (Azov Sea) and on Dzharylgach Island (Black Sea). In the course of research from 1988 –2014, deer were predominately observed with wedgeshaped (32.2 %), basket-shaped (23.6 %), and rounded and widely-spaced (21.6 %) antlers. In adult deer antler length ranged 70.0 –117.0 cm. 98.6 % of them had developed brow tines, and 49.1 % had developed bay tines. In the 1970s, the best antlers were evaluated at 210 –258 points, and from 1988–2014 at 143.90 –166.27 points (CIC). This indicates a decline in the trophy quality of deer of Askanian origin, which calls for the implimentation of biotechnical measures and selective intervention in all populations.
Keywords: antler; area; hybridation; hunting; mammals; management; population; red deer; steppe zone; trophy; Ukraine